Clinical and Diagnostic Features of Bronchial Asthma in Children on the Background of Latent Food Allergy - V.M. Levytskyi; E.V. Yurchyshena; O.M. Yurchyshen; L.V. Mysko; Yu.L. Mysko (Zaslavsky O.Yu., 2015)
Based on clinical and paraclinical examination of 112 children with bronchial asthma, there were studied the features of its course against the background of food allergy. It was found that only a set of clinical and paraclinical signs is the most important for the diagnosis of bronchial asthma in children on the background of latent food allergy.